ANALISIS KARAKTERISTIK KECERDASAN VISUAL SPASIAL SISWA DALAM MENYELESAIKAN SOAL PISA KONTEN SHAPE AND SPACE DITINJAU DARI TIPE KEPRIBADIAN MENURUT DAVID KEIRSEY - Nuraini, Ais; Sunardi, Sunardi; Ambarwati, Reza; Hobri, Hobri; Jatmiko, Dhanar Dwi Hary (Kadikma, 2022)
This study aims to describe students' spatial-visual ability in solving PISA questions in shape and space content based on David Keirsey's personality type are guardian, artisan, idealist, and rational. This type of research used in this research is descriptive qualitative research. Subjects in the study were eight students from Class XI MIPA 1 SMA Negeri 7 Kediri consisting of two students from each of the guardian, artisan, idealist, and rational personality type. The data collection methods used were questionnaires, tests, and interviews. The instruments used in this study were MBTI questionnaires, shape and space content PISA test questions, and interview guidelines. The results showed that the achievement of the characteristics of the eight spatial-visual abilities of the subjects differed. Students with guardian personality are able to fulfill two characteristics of visual-spatial intelligence consisting of pattern search and conceptualization, but unable to fulfill the characteristics of problem-solving and imagining. Students with artisal personality are able to fulfill two characteristics of visual-spatial intelligence which consist of pattern searching and imagining. Students with idealist personality are able to fulfill the three characteristics of visual spatial intelligence which consist of pattern searching, conceptualizing, and imagining. Students with rational personality are able to fulfill all the characteristics of visual abilities consisting of pattern search, conceptualization, problem solving, and complete imagination in solving shape and space content PISA questions. This can be seen from the results of solving the questions given and interviews conducted on the research subjects.